Twelve-Week Game-Based School Intervention Improves Physical Fitness in 12–14-Year-Old Girls - Petrušič, Tanja; Trajković, Nebojša; Bogataj, Špela (Frontiers in Public Health, 2022)
The aim of this study was to determine the effects of a twelve-week game-based school intervention on physical fitness in girls aged 12-14 years. Fifty-nine adolescent girls (13.2 ± 0.3 years) were randomly assigned to a group that participated in a game-based after-school program (EXP) or a control group (CON) that participated only in mandatory physical education. The EXP group had the additional program twice a week after school for 40 minutes/session for 12 weeks alongside with regular physical education classes. The EXP program consisted mainly of small-sided games of football, basketball, handball, and volleyball. The assessment included a physical fitness assessment with standardized tests for this age group: countermovement jump (CMJ), standing long jump, bent arm hang, overhead medicine ball throw, sit-ups for 30 seconds, and Yo-Yo Intermittent Recovery Level 1 Test (YYIRT1). There was a significant interaction between group (EXP vs. CON) and time (pre-test vs. post-test) for the standing long jump (p < 0.001), overhead medicine ball throw (p < 0.001), 30-second sit-ups (p = 0.030), bent- arm hang (p < 0.001), and YYIRT1 score (p = 0.004). In addition, a significant main effect was found for time in countermovement jump (p < 0.001). The results of this study indicate that the after-school game-based intervention significantly improves adolescent girls' physical fitness compared to regular physical education. The overall conclusion suggests that as few as two additional sessions per week are sufficient to produce significant changes in physical fitness in adolescent girls.